A rapid quantitative dye-binding method of screening glycosaminoglycans presence in medicinal plants - Che Nur Mazadillina, Zahari; Marina, Mohd Sham; Sakina, Shahabudin; Mohd Hairul, Ab. Rahim; Nina Suhaity, Azmi (Innovare Academic Sciences Pvt Ltd, 2019)
Objectives: The aims of this paper are to extract glycosaminoglycan (GAG) from four local medicinal plants and to characterize the crude extract with highest total sulfated GAG in order to reduce the dependency of using animals as major sources. Methods: Crude GAG was extracted from four plants (Gaultheria procumbens, Strobilanthes crispus, Orthosiphon stamineus and Ficus deltoidea) using hot water extraction with some modifications. Ultraviolet (UV) spectrophotometry was conducted for purity test. Total sulfated GAG was determined by using Blyscan assay kit. By comparing results between the extract yields and total sulfated GAG, the plant consisting of high total sulfated GAG was chosen for further characterization. The selected plant sample was examined by microscopy and further analyzed by nuclear magnetic resonance (NMR) and Fourier-transform infrared (FTIR) spectroscopy. Results: All four plants showed absorbance peaks between 214 and 232 nm in UV scan that represented negatively charged sugar. O. stamineus was found to contain the highest amount of sulfated GAG, 62.63 ± 0.01 µg/mg by Blyscan assay. Microscopical examination confirmed the identity of O. stamineus sample by comparing to the reference. Both NMR and FTIR analysis of O. stamineus crude yield showed presence of hydroxyl, sulfates, carboxylate, and amine groups, suggesting close resemblances to GAG structure. Conclusion: The results suggested that all four plants contained GAG compound. O. stamineus was found to exhibit the most abundant total sulfated GAG, and has potential to become a new plant-based source for GAG.